Inelastic torsion of multistorey buildings under earthquake excitations. - Stathopoulos, K.G (Earthquake engineering & structural dynamics.)
The inelastic earthquake response of eccentric, multistorey, frame-type, reinforced concrete buildings is investigated using three and five storey models, subjected to a set of 10, two-component, semi-artificial motions, generated to match the design spectrum. Buildings designed according to the EC8 as well as the UBC-97 code were included in the investigation. It is found that contrary to what the simplified one-storey, typical, shear beam models predict, the so-called 'flexible' side frames exhibit higher ductility demands than the 'stiff' side frames. The substantial differences in such demands between the two sides suggest a need for reassessment of the pertinent code provisions. This investigation constitutes one of the first attempts to study the problem of inelastic torsion by means of realistic, multistorey inelastic building models. Additional studies with similar or even more refined idealizations will certainly be required to arrive at definite results and recommendations for possible code revisions.